2006
DOI: 10.1371/journal.pbio.0040348
|View full text |Cite|
|
Sign up to set email alerts
|

A Signaling Network for Patterning of Neuronal Connectivity in the Drosophila Brain

Abstract: The precise number and pattern of axonal connections generated during brain development regulates animal behavior. Therefore, understanding how developmental signals interact to regulate axonal extension and retraction to achieve precise neuronal connectivity is a fundamental goal of neurobiology. We investigated this question in the developing adult brain of Drosophila and find that it is regulated by crosstalk between Wnt, fibroblast growth factor (FGF) receptor, and Jun N-terminal kinase (JNK) signaling, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
64
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(67 citation statements)
references
References 74 publications
2
64
1
Order By: Relevance
“…Alternatively, JNK activation may act as a reprogramming signal allowing neurons to reactivate their specific developmental pathways. Although we do not exclude a role for JNK in axonal navigation, our previous work (Leyssen et al, 2005;Srahna et al, 2006) shows that JNK can stimulate different cell types to grow longer axons, without influencing their guidance properties. In this context, it may seem surprising that the induction of JNK signaling observed during axonal injury (Leyssen et al, 2005) is not sufficient to induce regeneration.…”
Section: Jnk Signaling Regulates Axonal Regenerationmentioning
confidence: 57%
See 2 more Smart Citations
“…Alternatively, JNK activation may act as a reprogramming signal allowing neurons to reactivate their specific developmental pathways. Although we do not exclude a role for JNK in axonal navigation, our previous work (Leyssen et al, 2005;Srahna et al, 2006) shows that JNK can stimulate different cell types to grow longer axons, without influencing their guidance properties. In this context, it may seem surprising that the induction of JNK signaling observed during axonal injury (Leyssen et al, 2005) is not sufficient to induce regeneration.…”
Section: Jnk Signaling Regulates Axonal Regenerationmentioning
confidence: 57%
“…First, JNK is a general stress response pathway (Leppa and Bohmann, 1999). Second, we have shown that JNK signaling is necessary and sufficient for axonal extension in the fly CNS (Srahna et al, 2006) and that it is transiently induced by brain injury in Drosophila (Leyssen et al, 2005). Third, c-Jun is necessary for spontaneous regeneration in the mouse PNS (Raivich et al, 2004).…”
Section: Activated Jnk Signaling Induces Regeneration Back Into the Omentioning
confidence: 99%
See 1 more Smart Citation
“…We asked whether DenMark could be used to identify the dendritic compartments of sparse or individual neurons by labeling the dorsal cluster neurons (DCNs) in the adult brain (38) and a pair of eclosion hormone (EH) positive neurons in the third instar larva. DCN axons innervate the lobula and medulla of the optic lobes contralaterally, whereas their dendrites have been proposed to innervate the ipsilateral lobula only (39). Syt:: GFP and DenMark were expressed in the DCN and their patterns examined (Fig.…”
Section: Denmark Reveals Progressive Developmental Specialization Ofmentioning
confidence: 99%
“…As a member of the JIPs, JIP3 has been suggested to tether specific JNK signaling modules, thereby promoting signal transmission (3)(4)(5)(6). The JNK pathway is involved in axon formation/polarization, extension, synaptic plasticity, and dendrite development (7)(8)(9)(10)(11). Moreover, as a homology of UNC-16 in Caenorhabditis elegans and Sunday Driver in Drosophila, JIP3 is implicated as an adaptor protein in kinesin-dependent vesicular transport to axons (12,13) and has recently been reported to be a mediator in TrkB anterograde axonal transport in hippocampal neurons (14).…”
mentioning
confidence: 99%